Peningkatan Kemampuan Berpikir Tingkat Tinggi Siswa Melalui Pembelajaran Matematika Berbantuan LKPD Berbasis HOTS - Lucy Asri Purwasi; Nur Fitiyana (Jurnal Pendidikan Matematika:Judika Education, 2020)
The purpose of this study was to find out the improvement of students' high level of thinking ability through hots-based LKPD rocky mathematics learning. This research is a kuantitafif research with research design one group pretest -posttest design. This research instrument is a question of essays totaling 3 questions consisting of indicators of tingi level thinking, namely analyzing, evaluating and creating. The sample selection was done in cluster random sampling with the selected sample is class VIII-2 which consists of 22 students. The data obtained were analyzed using unilateral t-tests. Based on the results of data analysis at a significant level of α = 0.05 obtained ρ value 0.033 with an average high level of thinking ability of students in grade VIII SMP Negeri 5 Lubuklinggau city is 74.09 with a good category. In conclusion, there is a significant increase in students' high-level thinking ability after doing LKPD-assisted mathematics lessons based on HOTS. Keywords: High Level Thinking, HOTS Based LKPD, Mathematics